ANALISIS INSTRUMEN TES KOGNITIF MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SD: ASPEK SUBSTANSI, KONSTRUKSI, BAHASA, DAN HIGH ORDER THINKING SKILL - Saepul Anwar; Udin Supriadi; Wawan Hermawan (Taklim : Jurnal Pendidikan Agama Islam, 2021)
AbstractThis paper results from first-year research on the Development of Cognitive Assessment Instruments Based on Higher Order Thinking Skills (HOTS) in Islamic Religious Education Subjects and Characteristics in Elementary Schools. The research focus in the first year is mapping Islamic education teachers' ability in elementary school to develop cognitive assessment instruments that include aspects of skills in constructing item questions and the distribution of thinking levels. The research method used in this research is quantitative-descriptive and document analysis in the form of a multiple-choice PAI test instrument. The documents collected were 29 question packages. The twenty-nine question packages for PAI and Character courses consist of 1 question package for grade 2 SD, 11 question packages for grade 4 SD, 10 question packages for grade 5 SD, and 7 question packages for grade 6 SD. At the same time, the data analysis used descriptive statistics in the form of percentages. The study results concluded that most of the objective question packages were in the form of Multiple Choice Items (MCI) in Islamic Education and Characteristics in Elementary School subjects, which were considered good in most of the indicators in every aspect. However, the most prominent weakness is preparing answer options, both in the substance aspect (the option homogeneity criteria), which only reaches 72%, and the construction aspect (the option sentence length criteria), which only reaches 73%. Besides that, the emergence of questions that measure the cognitive processes of the reasoning level (C4, C5, and C6), which only appeared in 2 of the 29 question packages analyzed. Even then, the proportion is only 1% of the number of question items in each package.Keywords: Multiple Choice Items, Cognitive Assessment Instruments, Higher Order Thinking Skills, Islamic Religious Education in Elementary Schools Abstrak Tulisan ini merupakan hasil riset tahun pertama tentang Pengembangan Instrument Penilaian Kognitif Berbasis Higher Order Thinking Skills (HOTS) Pada Mata Pelajaran Pendidikan Agama Islam Dan Budi Pekerti Di Sekolah Dasar. Fokus riset pada tahun pertama adalah pemetaan kemampuan guru PAI SD dalam menyusun instrumen penilaian kognitif yang meliputi aspek keterampilan dalam mengkonstruksi item soal dan sebaran tingkat berpikir. Metode penelitian yang digunakan dalam penelitian ini adalah kuantitatif-deskriptif dan analisis dokumen berupa Instrumen tes PAI berbentuk pilihan berganda. Dokumen yang terkumpul sebanyak 29 paket soal. Kedua puluh sembilan paket soal mata kuliah PAI dan Budi Pekerti tersebut terdiri dari 1 paket soal kelas 2 SD, 11 paket soal kelas 4 SD, 10 paket soal kelas 5 SD, dan 7 paket soal kelas 6 SD. Sementara analisis data menggunakan statistik deskriptif berupa prosentase. Hasil penelitian menyimpulkan bahwa sebagian besar paket soal objektif berbentuk Multiple Choice Item (MCI) mata pelajaran PAI dan Budi Pekerti di SD terbilang sudah baik dalam sebagian besar indikator pada setiap aspeknya. Hanya saja, kelemahan yang paling menonjol ada pada penyusunan opsi jawaban, baik pada aspek substansi (kriteria homogenitas opsi) yang hanya mencapai 72% dan aspek konstruksi (kriteria panjang pendeknya kalimat option) yang hanya mencapai 73%. Disamping itu kemunculan soal-soal yang mengukur proses kognitif level penalaran (C4, C5, dan C6) yang hanya muncul di 2 paket soal dari 29 paket soal yang dianalisis. Itupun proporsinya hanya 1% dari jumlah item soal pada setiap paketnya.Kata Kunci:  Multiple Choice Item, Instrumen Penilaian Kognitif, Higher Order Thinking Skills, Pendidikan Agama Islam di Sekolah Dasar